Elite portuguese soccer players` use of psychological techniques: where, when and why - Fernandes de Freitas, S. P.; Lima Dias, C. S.; Ferreira Leal Mendoça da Fonseca, A. M. (Journal of Human Sport & Exercise, 2013)
The purpose of the current study was to examine the use whether, were, when and why soccer players used self-talk, imagery, goal setting and relaxation. Semi-structure, in-depth, qualitative interviews were conducted with 16 elite soccer players from Portuguese premier league soccer teams that played regularly in UEFA champions and Europe leagues. Results demonstrated that participants employed self-talk, goal-setting, and imagery with several purposes in their soccer routines. On the other hand, participants highlighted a lack of use of relaxation. In addition, results showed that the use of psychological techniques was lower in training than competition setting. Implications of the results are discussed and future research and practical recommendations are suggested.